Penerapan Augmented Reality sebagai Penampil Model 3D Rumah Berbasis Android pada The East View Residence - Ibrahim Renata, Roby; Gatc, Jullend (KALBISCIENTIA Jurnal Sains dan Teknologi, 2020)
The East View Residence is an existing home product in Kota Bekasi, with rapidly growinginfrastructure development in Bekasi City makes The East View Residence needs to compete with theother competitors. Utilization of augmented reality technology in the field of business is not a newthing, especially in the field of marketing. This research aims to develop an Android-based augmentedreality app that able to utilize brochures as a target image in displaying information related to homeproducts offered by The East View Residence with Iterative Development approach. Based on the resultsand evaluation, this research succeeded in implementing Iterative Development research method indeveloping an application which is utilized for interesting and interactive marketing activities andgiving added value to the brochure media itself.